Dampak Korupsi Terhaadap Pembangunan Ekonomi Dan Pembangunan Politik - Wahyuningsih, Tresita; Hasanah, Syariatun; Albadani, Qiya; Alawiyah, Miranda (Lembaga Riset dan Publikasi, 2025)
Corruption is a serious issue that hinders economic growth and political stability, particularly in developing countries like Indonesia. Widespread corruption not only causes financial losses to the state but also degrades the quality of public services, weakens democratic institutions, and erodes public trust in the government. This study aims to analyze the impact of corruption on economic and political development, and to provide policy recommendations that can help reduce corruption systematically. The research offers academic value as a scientific reference and practical relevance for policymakers and the public in formulating effective anti-corruption strategies. A descriptive qualitative method is used with a literature study approach, based on reports from anti-corruption agencies, scholarly journals, official statistics, and policy documents. The findings reveal that corruption reduces budget efficiency, discourages investment, and worsens the quality of infrastructure and public services. Politically, corruption weakens democracy, lowers public participation, and increases the risk of governmental instability. Therefore, combating corruption is a crucial step in achieving sustainable development and ensuring a transparent and accountable government.